The Effects of Emotional Intelligence and Parenting Styles on Self-Esteem in a Sample of Respondents in Nigeria - Fakunmoju, Sunday; Bammeke, Funmi; Maphosa, Ntandoyenkosi (Technium Social Sciences Journal, 2021)
Studies consistently suggest that emotional intelligence and parenting styles are associated with self-esteem, although validation has relatively been based on correlation analysis. Using a sample of 252 respondents in Nigeria, the present study examined the relationships among parenting styles, emotional intelligence, and self-esteem with the aim of generating knowledge that transcends the nature and extent of their correlations. A bivariate analysis identified significant correlations: emotional intelligence (i.e., self-emotion appraisal, others’ emotion appraisal, uses of emotion, and regulation of emotion), authoritative parenting, and authoritarian parenting significantly positively correlated with self-esteem. There was no significant correlation between emotional intelligence and parenting styles. Results of the independent-samples t test indicated that emotional intelligence and self-esteem differed by gender. Specifically, women were more likely than men to report high self-emotion appraisal, others’ emotion appraisal, and uses of emotion. Similarly, women were more likely than men to report high self-esteem. Using multiple regression analysis, emotional intelligence and parenting styles were associated with self-esteem: being a student, emotional intelligence (i.e., self-emotion appraisal and uses of emotion), and authoritative parenting were associated with self-esteem. Emotional intelligence accounted for a larger effect on self-esteem than did parenting styles. In general, findings lend credence to the relevance of authoritative parenting in the development of self-esteem and suggest that, among components of emotional intelligence, uses of emotion and self-emotion appraisal may be considered in facilitating improvement of self-esteem among young adults at the developmental stage of increasing self-esteem. Implications of findings for research, education, and practice are discussed.